Precise measurement of coronary stenosis diameter with CCTA using CT number calibration. Issue 12 (31st October 2019) - Chen, Zhennong; Contijoch, Francisco; Schluchter, Andrew; Grady, Leo; Schaap, Michiel; Stayman, Web; Pack, Jed; McVeigh, Elliot
Abstract : Purpose: Coronary x‐ray computed tomography angiography (CCTA) continues to develop as a noninvasive method for the assessment of coronary vessel geometry and the identification of physiologically significant lesions. The uncertainty of quantitative lesion diameter measurement due to limited spatial resolution and vessel motion reduces the accuracy of CCTA diagnoses. In this paper, we introduce a new technique called computed tomography (CT)‐number‐Calibrated Diameter to improve the accuracy of the vessel and stenosis diameter measurements with CCTA. Methods: A calibration phantom containing cylindrical holes (diameters spanning from 0.8 mm through 4.0 mm) capturing the range of diameters found in human coronary vessels was three‐dimensional printed. We also printed a human stenosis phantom with 17 tubular channels having the geometry of lesions derived from patient data. We acquired CT scans of the two phantoms with seven different imaging protocols. Calibration curves relating vessel intraluminal maximum voxel value (maximum CT number of a voxel, described in Hounsfield Units, HU) to true diameter, and full‐width‐at‐half maximum (FWHM) to true diameter were constructed for each CCTA protocol. In addition, we acquired scans with a small constant motion (15 mm/s) and used a motion correction reconstruction (Snapshot Freeze) algorithm to correct motion artifacts. We applied our technique to measure the lesion diameter in the 17 lesions in the stenosis phantom and compared the performance of CT‐number‐Calibrated Diameter to the ground truth diameter and a FWHM estimate. Results: In all cases, vessel intraluminal maximum voxel value vs diameter was found to have a simple functional form based on the two‐dimensional point spread function yielding a constant maximum voxel value region above a cutoff diameter, and a decreasing maximum voxel value vs decreasing diameter below a cutoff diameter. After normalization, focal spot size and reconstruction kernel were the principal determinants of cutoff diameter and the rate of maximum voxel value reduction vs decreasing diameter. The small constant motion had a significant effect on the CT number calibration; however, the motion‐correction algorithm returned the maximum voxel value vs diameter curve to that of stationary vessels. The CT number Calibration technique showed better performance than FWHM estimation of diameter, yielding a high accuracy in the tested range (0.8 mm through 2.5 mm). We found a strong linear correlation between the smallest diameter in each of 17 lesions measured by CT‐number‐Calibrated Diameter (DC ) and ground truth diameter (Dgt ), (DC  = 0.951 × Dgt  + 0.023 mm, r = 0.998 with a slope very close to 1.0 and intercept very close to 0 mm. Conclusions: Computed tomography‐number‐Calibrated Diameter is an effective method to enhance the accuracy of the estimate of small vessel diameters and degree of coronary stenosis in CCTA.